Some Observations of Waves at the Hong Kong International Airport and Their Numerical Simulations - Pak Wai Chan; Kai Kwong Lai; Ping Cheung; Yan Yu Leung (Atmosphere)
Because of terrain disruption of the airflow and interface between different airmasses, wave motions may be observed in the vicinity of the Hong Kong International Airport using plan position indicator scans and range height indicator scans with Doppler light detection and ranging systems. This paper documents three cases of wave motion that are not commonly observed near this airport and have never been described before in the literature for Hong Kong, including one mountain wave case and two cases of interfaces between airmasses. These waves may have impacts on aviation safety by leading to the occurrence of low-level windshear and turbulence. They are studied further using a high-resolution numerical weather prediction model. It is found that the model is capable of capturing some features of the waves, such as their occurrence mechanisms. However, some details of the waves are not successfully reproduced, such as the changes in the number of wave crests/troughs with time. Further study should also be conducted to reproduce the wavelengths of these waves.